Penyeragaman dan Wajah Buram Modernitas di Kota Makassar pada Masa Orde Baru - I. Ilham (Department of History, Faculty of Humanities, Diponegoro University, 2019)
This article describes modernity in the city of Makassar during the New Order era. The meaning of modernity in this article was a modern idea or thought in the form projects of development (modernization) which the state tries to control. The control of the State is manifested in the form of uniformity and mobilization of development projects by the city government. The main impact that arises from the process is problems of urban, environment of the urban physical and social life of population of the city. This study uses the approach of the history of the city. The data used came from archives, newspapers, magazines, and results of interviews. This study shows that uniformity and mobilization of urban development modernity projects touch the lowest level, especially in the regulation and use of urban space and in the activities of urban residents. At the same time, the control and influence of the private sector increasingly determines the use of space. A predetermined city plan often can not work because it gets intervention from the interests of the private sector. In this conflict of interests, various